STUDENTS' LEARNING ABILITY IN WORKING ON HOTS (HIGHER ORDER THINKING SKILLS) IN MATHEMATICS LEARNING IN CLASS V SD NEGERI 040457 BERASTAGI - D. Yuliana Sinaga; Hetdy Sitio (Sensei International Journal of Education and Linguistic, 2023)
HOTS (Higher Order Thinking Skills) is an instrument that assesses students' hight level thinking skills so that students are not just remembering but are expected to be able to develop ideas. Based on Bloom's Taxonomy, HOTS questions consist of 3 levels, namely analyzing, evaluating and creating. This study aims to describe the ability of students to work on HOTS (Higher Order Thinking Skills) problems in mathematics learning in V class SD Negeri 040457 Berastagiat the level of analyzing, evaluating, and creating. This research uses a descriptive quantitative research design. The data of this study were obtained using tests of the students' ability to work on HOTS questions in mathematics learning provided to students by using content validity, while data analysis was performed using descriptive statistical analysis. The results showed that the ability of V grade students of SD Negeri 040457 Berastagi in working on HOTS questions in mathematics learning at the level of analyzing questions was obtained on average by 56.35 with quite good categories. In the matter of evaluating level obtained an average of 73,3 with a high category, on the matter of creating level obtained an average of 65,65 with a pretty good category. The conclusion of this research is the ability of V class students of SD Negeri 040457 in working on HOTS questions in mathematics learning is in quite good category, meaning that students are able to work on HOTS questions in mathematics learning.